(untitled) - Worsley, Peter (Chicago, 1964)
Today the colonial empires of the world are shrinking, and the new nations which have emerged from the colonial past are rapidly developing into an important force in international affairs the "third world." They are faced by a common problem, the urgent necessity to transform a peasant society into a modern industrial economy, and they are united by a common outlook, absolute opposition to all forms of colonialism and neocolonialism.In this work Peter Worsley analyzes the unique political forms that have evolved as a result of these two basic conditions. In his view the third world has rejected both of the great ideologies of today. Their new solutions are unique in world history, being based on populism, socialism, and, often, the one-party state, which, although anathema to the Western liberal, is a natural development in societies united by the common enemy of colonialism.
Keywords: Châu Phi, vùng Saharan,Africa, Sub-Saharan; Chính trị và chính phủ,Politics and government